Phytochemical fingerprinting of Nyctanthes arbor-tristis Linn. leaves by using FTIR and HPTLC analysis - Rahul, A N; Pratibha, F D (Plant Science Today, 2026)
The present study aimed to qualitatively fingerprint the methanolic leaf extract of Nyctanthes arbor-tristis Linn. to characterise its major bioactive phytoconstituents and establish a standardised chromatographic profile. The powdered material of NAT contains 14 different phytoconstituents, which were observed to exhibit various functional groups, including aliphatic amines, aromatic alcohols, phenols, polyphenols and flavonoids, as well as aliphatic compounds, alkanes, alkyl halides and alkynes, represented by distinct peaks in the FTIR graphical representation. At 369.04 to 2920.72, was analysed in different cmˉ1 ranges. Qualitative phytochemical screening was performed to detect key secondary metabolites, followed by fourier transform infrared (FTIR) spectroscopy for functional group identification and high-performance thin layer chromatography (HPTLC) for chromatographic fingerprinting. Preliminary phytochemical analysis confirmed the presence of biologically important constituents, including glycosides, flavonoids, terpenoids, phenols, tannins, steroids and saponins. FTIR analysis revealed multiple functionally active groups such as phenols, polyphenols, flavonoids, aliphatic and aromatic compounds, amines, alkanes and alkyl halides, indicating a chemically diverse phytochemical composition. HPTLC fingerprinting using ethanol: n-hexane: chloroform (4:2:4) as the mobile phase generated reproducible chromatographic profiles at 254 nm and 366 nm, demonstrating the presence of multiple secondary metabolites at varying concentrations. The combined FTIR and HPTLC analyses establish a reliable phytochemical fingerprint of N. arbor-tristis leaves and confirm their richness in bioactive constituents. These findings provide a scientific basis for quality control, standardisation and further isolation of pharmacologically active compounds, supporting the therapeutic relevance of this medicinal plant.